The Philosophy of History and the Idea of Decadence - Quispe Pari, César Alberto (2023)
The Philosophy of History has raised the study of the final end of time as a recurring theme. Humanity has considered various ways of understanding this end, however, no category of study has generated greater interest than the analysis of decadence, since everything tends to fall sooner or later, including humanity itself.